2012
DOI: 10.1093/ndt/gfr809
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine generation is reduced in patients requiring continuous venovenous hemodialysis and independently predicts mortality

Abstract: Grading systems for severity of AKI fail to account for variation in CGR, limiting their ability to predict relevant outcomes. Calculation of CGR is superior to other risk metrics in predicting hospital mortality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…Critically ill patients who have suffered AKI, experienced a significant decrease in creatinine generation [10,11] not only during their illness but also at the time of hospital discharge, and then weeks into their recovery. This means it is likely that estimates of creatinine generation, implicit in eGFR equations, are poorly calibrated to this group; eGFR could therefore significantly overestimate true GFR in many survivors of critical illness for a significant period after the acute illness [5].…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients who have suffered AKI, experienced a significant decrease in creatinine generation [10,11] not only during their illness but also at the time of hospital discharge, and then weeks into their recovery. This means it is likely that estimates of creatinine generation, implicit in eGFR equations, are poorly calibrated to this group; eGFR could therefore significantly overestimate true GFR in many survivors of critical illness for a significant period after the acute illness [5].…”
Section: Discussionmentioning
confidence: 99%
“…At higher creatinine generation rate, the rate of creatinine rise in AKI is greater. Creatinine generation rate is a proxy for muscle mass, and higher levels may identify a healthier subset of patients with AKI (31). It has been suggested that creatinine generation rate may be increased by catabolic states, although this has not been measured in AKI populations to our knowledge (32).…”
Section: Creatinine Kinetics and Dialysis In Akimentioning
confidence: 99%
“…However, large improvements in GFR from baseline after critical illness would seem implausible, whereas large and sustained falls in creatinine generation have been shown in animal models of sepsis (14), patients with advanced CKD (15), and critically ill humans (16)(17)(18), with greatest decrease occurring in the sickest patients (16). Skeletal muscle is the major source of creatinine production, and critical illness is associated with profound loss of skeletal muscle protein (10,19,20), with muscle thickness steadily decreasing over time after ICU admission (10,21,22).…”
Section: Study Findingsmentioning
confidence: 99%